Social prescribing for individuals with mental health problems: An ethnographic study exploring the mechanisms of action through which community groups support psychosocial well-being [version 1; peer review: 1 approved, 2 approved with reservations] - Helen Chatterjee; Henry Aughterson; Alexandra Burton; Daisy Fancourt (Wellcome Open Research, 2024)
Background Social prescribing involves connecting individuals to community groups and activities, often to support their mental health and well-being. It has received increasing support in recent years across the NHS. There is a strong evidence base for the benefits of different types of community activities, including exercise groups, arts groups and nature interventions, on mental health outcomes, however, less is known about how these groups impact mental health and well-being. This study explores through what individual-level mechanisms (the ‘how’) these groups support psychosocial well-being. Methods An ethnographic study was conducted over 12-months to explore key shared, individual-level mechanisms across 4 social prescribing community groups: football, singing, gardening and reading. This study focused mostly on those with severe mental illness, whereas previously most social prescribing studies have focused on mild to moderate mental health problems. To frame the findings, a ‘multi-level theoretical framework of mechanisms of action’ of leisure activities was used. Results Key shared psychological mechanisms were: increased self-confidence and self-esteem, increased purpose/meaning, increased sense of achievement, experience of pleasure; social mechanisms included: increased social support, formation of friendships and reduced loneliness, enhanced sense of community and belonging; behavioural mechanisms were: increased independence and openness to experience, reduction in addictive behaviours and building healthier habits, increased work-seeking behaviour, and provision of structure & routine. Conclusions It is hoped that the findings of this study can help referring professionals increase their understanding of exactly how such groups support individuals’ mental health, thus enhancing referring practices.